2015
DOI: 10.1016/j.biopsych.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cortical Network Oscillations and Parvalbumin Neurons in Schizophrenia

Abstract: Cognitive deficits are a core clinical feature of schizophrenia but respond poorly to available medications. Thus, understanding the neural basis of these deficits is crucial for the development of new therapeutic interventions. The types of cognitive processes affected in schizophrenia are thought to depend on the precisely timed transmission of information in cortical regions via synchronous oscillations at gamma band frequency. Here, we review 1) data from clinical studies suggesting that induction of front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
305
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(340 citation statements)
references
References 147 publications
14
305
1
6
Order By: Relevance
“…During working memory tasks, excitation from pyramidal neurons recruits PV interneurons, which in turn provide phasic inhibition that synchronizes the firing of pyramidal neurons at gamma frequency (14). Due to the narrow time window of PV interneuron recruitment during gamma oscillations, PV interneurons require efficient detection of glutamatergic inputs with high precision (15,16).…”
mentioning
confidence: 99%
“…During working memory tasks, excitation from pyramidal neurons recruits PV interneurons, which in turn provide phasic inhibition that synchronizes the firing of pyramidal neurons at gamma frequency (14). Due to the narrow time window of PV interneuron recruitment during gamma oscillations, PV interneurons require efficient detection of glutamatergic inputs with high precision (15,16).…”
mentioning
confidence: 99%
“…In addition to abnormal glutamatergic neurotransmission, mounting evidence suggests that impaired γ-aminobutyric acid (GABA)ergic neurotransmission, at least in part, mediates the cognitive deficits in schizophrenia Lewis et al 2012;Gonzalez-Burgos et al 2015). Coordinated activity of excitatory pyramidal cells and GABAergic interneurons, in particular via fast-spiking parvalbumin (PV) interneurons, govern the synchronisation of gammaoscillations within the PFC (Gonzalez-Burgos and Lewis, 2012), and NMDARs expressed in PV interneurons are critical for induction of gamma-oscillations and behaviour (Sohal et al 2009;Carlén et al 2012;Belforte et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that repeated, intermittent administration of esketamine, but not R-ketamine, caused loss of PV-immunoreactivity in the prefrontal cortex of mouse brain (Yang et al 2016). Since loss of PV-immunoreactivity in the prefrontal cortex may be associated with psychosis and γ-oscillation deficits in schizophrenia (Gonzalez-Burgos et al 2015), it is possible that repeated administration of esketamine or ketamine may have long-lasting detrimental side effects in the prefrontal cortex of humans.…”
mentioning
confidence: 99%